2017
DOI: 10.1097/dcr.0000000000000770
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Resection is a Good Prognostic Factor in Rectal Cancer Compared with Laparoscopic Resection: Long-term Survival Analysis Using Propensity Score Matching

Abstract: BACKGROUND: Robotic total mesorectal excision for rectal cancer has rapidly increased and has shown short-term outcomes comparable to conventional laparoscopic total mesorectal excision. However, data for long-term oncologic outcomes are limited. OBJECTIVE: The aim of this study is to evaluate long-term oncologic outcomes of robotic total mesorectal excision compared with laparoscopic total mesorectal excision. DESIGN: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
76
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 118 publications
(83 citation statements)
references
References 30 publications
6
76
1
Order By: Relevance
“…Historically, open rectal resection and TME had been considered technically difficult, especially in the narrow pelvis . With improved technology including laparoscopy, robotics, and energy devices, there has been a shift towards minimally invasive TME with better patient recovery and reduced length of stay at hospital . However, there have been concerns over the quality of TME in minimally invasive techniques .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Historically, open rectal resection and TME had been considered technically difficult, especially in the narrow pelvis . With improved technology including laparoscopy, robotics, and energy devices, there has been a shift towards minimally invasive TME with better patient recovery and reduced length of stay at hospital . However, there have been concerns over the quality of TME in minimally invasive techniques .…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the improvements in laparoscopy and robotics including improved ergonomics, magnified view, and stable camera platform, minimally invasive TME requires good technical skills and has a steep learning curve, especially in very low rectal resections. Transanal TME (taTME), a “down‐to‐up” procedure, has been suggested as an alternative procedure, but early reports have been viable, and long‐term oncological results are still under review …”
Section: Introductionmentioning
confidence: 99%
“…The ROLARR subgroup analysis suggests a similar trend of lower conversion in high-risk cases. Moreover, Kim et al [19] recently reported a trend towards improved overall survival and cancer-specific survival with robotic resection for mid-to low-rectal cancer (mean tumour height from the anal verge was 6.8 cm) compared with laparoscopic resection. On univariate and multivariate analysis the robotic approach was a significant positive prognostic factor.…”
mentioning
confidence: 99%
“…The literature has been predominantly limited to level 3 evidence thus far. Matched comparisons by Kim et al [7] and Cho et al [8] have not shown statistically significant differences in 5-year overall survival or disease-free survival between robotic and laparoscopic colorectal surgery, although Kim et al [7] did demonstrate a trend to improved survival.…”
mentioning
confidence: 99%
“…Apart from improvements in short-term outcomes and conversion rates, using our own data and experience, we reported on the long-term outcomes of robotic and laparoscopic total mesorectal excision for mid and low rectal cancers (robotic, n=272; laparoscopic, n=460), showing that the robotic procedure is a positive prognostic factor in rectal cancer surgery [7]. Our study was the first in the literature to do so.…”
mentioning
confidence: 99%